Comparative assessment of the in vitro sensitivity of Brugia malayi infective larvae to albendazole, diethylcarbamazine and ivermectin alone and in combination. - Tippawangkosol P. (2014)
The antifilaricidal drugs ivermectin (IVM), diethylcarbamazine (DEC), and albendazole (ALB), used alone or in combinations against infective third-stage larvae (L3) of nocturnally subperiodic (NSP) Brugia malayi (Narathiwat strain), were tested in vitro for sensitivity, for 7 days. IVM alone reduced larval motility at concentrations of 10(-7), 10(-6), and 10(-5) M on day 3. DEC alone also had this effect at concentrations of 10(-6). 10(-5), and 10(-4) M on day 2. ALB alone did not have this effect throughout the experiment, at various concentrations. However, it had greater effect when used in combination with either DEC or IVM. The result also indicated that DEC or IVM, when used in combination with ALB at concentrations of 10(-6) M/10(-6) M, and 10(-5) M/10(-5) M was effectively better than each drug used alone at those concentrations. When both drug combinations were compared, ALB/DEC seemed to be more effective than ALB/IVM at a concentration of 10(-6) M/10(-6) M on day 3. Although IVM and DEC can reduce larval motility when used alone or in combination with ALB, they cannot kill these larvae in an in vitro cultivation, even at a high concentration (10(-5) M).